Design, synthesis, and antitumor activity evaluation of novel acyl sulfonamide spirodienones. (15th April 2022) - Chen, Chen; Luo, Yang; Yin, Honglu; Zhong, Qiu; Zheng, Shilong; Liu, Rui; Zhao, Chong; Wang, Guangdi; He, Ling
Graphical abstract: Abstract: Based on the promising results of benzenesulfonamide spirodienones as antineoplastic agents, we have designed and synthesized a series of novel acyl sulfonamides spirodienone for antineoplastic evaluation. Of these, compound 4a exhibited remarkable in vitro antiproliferative activity by arresting the cell cycle and inducing apoptosis of MDA-MB-231 cells. Acute toxicity study has demonstrated 4a at 100 mg/kg dose caused no obvious toxicity to the major organs of mice. Moreover, compound 4a suppressed the growth of murine 4T1 tumor in vivo . Preliminary enzyme assay showed that 4a was a potential MMP2 inhibitor for cancer therapy. In all, these results indicate that compound 4a may be a lead compound for the development of anticancer agents.